204k views
5 votes
Hi any chance that somebody can help me with 9, 10, and 11? Thank u so much for your help if you know how!!! ❤️

Hi any chance that somebody can help me with 9, 10, and 11? Thank u so much for your-example-1

1 Answer

4 votes

✿ Heya! Grace ✿

✿ Nice Flower Drawing ✿

9. Given : The Length of the Side of the Square is
\mathsf{: 48√(2)}

We know that : Area of a Square is given by : Side × Side


\mathsf{\implies The\;Area\;of\;the\;Given\;Square = (48√(2)) * (48√(2))}


\mathsf{\implies The\;Area\;of\;the\;Given\;Square = (48√(2))^2}


\mathsf{\implies The\;Area\;of\;the\;Given\;Square = (48)^2(2)}


\mathsf{\implies The\;Area\;of\;the\;Given\;Square = (2304)(2)}


\mathsf{\implies The\;Area\;of\;the\;Given\;Square = 4608\;Inch^2}

----------------------------------------------------

10. Given : The Length of Rectangular Prism
\mathsf{= √(5)\;feet}

Given : The Width of Rectangular Prism
\mathsf{= 2 + √(3)\;feet}

Given : The Height of Rectangular Prism
\mathsf{= 2 - √(3)\;feet}

We know that : Volume of a Rectangular Prism is given By :

✿ Length × Width × Height

⇒ Volume of the Given Rectangular Prism is :


\mathsf{(√(5)) * (2 + √(3)) * (2 - √(3))}


\mathsf{\implies (√(5)) * (2^2 - (√(3))^2)}


\mathsf{\implies (√(5)) * (4 - 3)}


\mathsf{\implies √(5)}

-------------------------------------------------------------

11. (a)

Given : The Length of First Leg
\mathsf{= 3 + √(3)\;feet}

Given : The Length of Second Leg
\mathsf{= 3 - √(3)\;feet}

We know that, From Pythagorean Theorem :

✿ (Hypotenuse)² = (First Leg)² + (Second Leg)²


\mathsf{\implies (Hypotenuse)^2 = (3 + √(3))^2 + (3 - √(3))^2}


\mathsf{\implies (Hypotenuse)^2 = (3^2 + (√(3))^2 + 2(3)(√(3)) + (3^2 + (√(3))^2 - 2(3)(√(3))}


\mathsf{\implies (Hypotenuse)^2 = [3^2 + (√(3))^2] + [3^2 + (√(3))^2]}


\mathsf{\implies (Hypotenuse)^2 = (2) [3^2 + (√(3))^2]}


\mathsf{\implies (Hypotenuse)^2 = (2) [9 + 3]}


\mathsf{\implies (Hypotenuse)^2 = (2)(12)}


\mathsf{\implies (Hypotenuse)^2 = 24}


\mathsf{\implies Hypotenuse = √(24)}


\mathsf{\implies Hypotenuse = 2√(6)}

(b). We know that Perimeter of a Triangle is given by Adding the Lengths of all the Three Sides of the Triangle.


\mathsf{\implies Perimeter\;of\;the\;Given\;Triangle = [(3 + √(3)) + (3 - √(3)) + 2√(6)]}


\mathsf{\implies Perimeter\;of\;the\;Given\;Triangle = [(3 + 3 + 2√(6)]}


\mathsf{\implies Perimeter\;of\;the\;Given\;Triangle = (6 + 2√(6))\;feet}

(c). We know that : Area of a Triangle is given by :


\mathsf{(1)/(2) * Base * Height}


\mathsf{\implies Area\;of\;Given\;Triangle = (1)/(2)(3 + √(3))(3 - √(3))}


\mathsf{\implies Area\;of\;Given\;Triangle = (1)/(2)[3^2 - (√(3))^2]}


\mathsf{\implies Area\;of\;Given\;Triangle = (1)/(2)[9 - 3]}


\mathsf{\implies Area\;of\;Given\;Triangle = (1)/(2)(6)}


\mathsf{\implies Area\;of\;Given\;Triangle = 3\;feet^2}

User Hammad Nasir
by
5.8k points